PENYUSUNAN LEMBAR KERJA SISWA (STUDENT WORK SHEET) UNTUK PEMBELAJARAN TARI PETERI BENSU TINGKAT SMP KELAS VII DI TAKENGON - Shera Utari; Irwansyah Irwansyah (Gesture: Jurnal Seni Tari, 2019)
ABSTRACT  This study aimed to develop a Student Work Sheet in learning Peteri Bensu dance for the seventh grade in Takengon. This study used the theory of Asra and Sumiati (2016: 171). For this reason, it took 3 stages in its preparation, namely: the planning stage, the implementation phase and the evaluation phase. The method used in this study was a qualitative method. The results of the study were in the form of a Student Work Sheet for VII grade in Peteri Bensu dance lessons. The preparation of this sheet was compiled based on the first semester of grade VII syllabus. The objective of this research was to produce Peteri Bensu Student Work Sheet which has been tested for its feasibility by material experts and media experts which meant it can be used by students as a guide for doing certain work that can enhance and strengthen the learning outcomes of Peteri Bensu dance material. The results of the average percentage by the experts in completing the evaluation sheet reached a value of 98.76% which was included in the category of very feasible to be used. Keywords: Preparation of Student Work Sheet, Peteri Bensu dance.     ABSTRAK            Penelitian ini bertujuan menyusun Lembar Kerja Siswa (Student Work Sheet) untuk pembelajaran tari Peteri Bensu tingkat SMP kelas VII di Takengon dengan menggunakan teori Asra dan Sumiati (2016: 171). Dalam penyusunannya dibutuhkan 3 tahapan yaitu: tahap perencanaan, tahap pelaksanaan dan tahap evaluasi. Metode yang digunakan pada penelitian ini adalah metode kualitatif. Hasil penelitian berupa produk Lembar Kerja Siswa (Student Work Sheet) pembelajaran tari Peteri Bensu tingkat SMP kelas VII. Penyusunan lembaran ini disusun berdasarkan silabus seni tari kelas VII semester satu. Ketercapaian penelitian menghasilkan Lembar Kerja Siswa (Student Work Sheet) tari Peteri Bensu yang telah diuji kelayakannya oleh ahli materi dan ahli media sehingga dapat digunakan oleh siswa sebagai panduan untuk mengerjakan pekerjaan tertentu mengenai materi tari Peteri Bensu. Hasil persentase rata-rata oleh para ahli dalam mengisi lembar evaluasi penilaian mencapai nilai 98,76% yang termasuk kedalam kategori sangat layak digunakan di lapangan. Kata Kunci : Penyusunan Lembar Kerja Siswa, tari Peteri Bensu.